Moderating the Company Value’s Determinants of Oil Palm Estate Company in Indonesia - Sinaga, Jhonni (Integrated Journal of Business and Economics (IJBE), 2025)
This study aims to gather evidence of the direct and indirect effects of the factors that determine a company's value, which are controlled by the dividend policy and corporate social responsibility (CSR). Purposive sampling determines the chosen samples. Refer to the performed recapitulations and calculations, there are only 5 companies of the 24 listed at IDX that meet the given criteria in 2009-2017. Using Structural Equation Modeling (SEM) utilizing a WarpPLS (Warp Partial Least Squares) approach we found that the capital structure has a negative and substantial impact on the company's worth during the years when the global economy was unstable and the price of products was declining.  By adopting optimal and consistent CSR activities and boosting dividend payouts to the optimal level, this effect can be lessened and transformed into something positive and important.  Increasing dividend payments steadily to the ideal level can likewise lessen or transform the positive and insignificant capital structure effect on the firm value through company growth into a positive and large one. Furthermore, because oil palm estate businesses have a three-year investment period, it is particularly crucial for management to carefully and accurately weigh the marginal benefits and costs of employing long-term bank loans or liabilities to finance business operations.